A Comparative Study on Effects of Laser, Ischemic Compression and Resisted Exercises Over Pain and Range of Motion among Patients with Chronic Trapezius Myalgia in Men - PONMATHI.P; M.MANIVANNAN; J.NARENDRAKUMAR; V.P.R.SIVAKUMAR (International Journal of Pharma and Bio Sciences, 2018)
Myofascial trigger point (MTPt) can be defined as a hyperirritable spot in skeletal muscle that is associated with a hypersensitive palpable nodule in a taut band. Myofascial trigger point is associated with pain on compression and the pain is typically of a referred type. They are at prevalence from 10% to 18% and lifetime prevalence from 30% to 50%. Myofascial trigger point symptoms cause severe discomfort and inability to work. Myofascial pain symptoms usually involve muscle pain with specific "trigger" or "tender" points. The pain is aggravated by activity or stress. This study aims to compare the effects of LASER, ischemic compression and Resisted exercises over pain in patients with Trapezius myalgia. Study design was Experimental, and the Study type was pre-test, post-test type. Inclusion criteria are males aged between 19 to 25 years and Trapezius stretch test was positive. Exclusion criteria are recent trauma and surgery in the neck. 30 Subjects are selected according to inclusion and exclusion criteria. Patients are divided into 3 groups. Group A underwent treatment with Ischemic compression, Group B underwent treatment with Therapeutic LASER and Group C with Resisted exercises for Trapezius muscle. An assessment was done on day 1 and day 5 of treatment, respectively. This study concludes that there exists no difference between LASER, Ischemic Compression and Resisted exercises. But clinically resistant exercises are found to be more effective than the other two modes of treatment over pain and increase in range of motion.